(untitled) - Eli Zuraida; Andi Masyitha Irwan; Elly Lilianty Sjattar (University of Ostrava, 2021)
Aim: To identify and evaluate self-management education programs. Design: A literature review. Methods: A search of five databases PubMed, ProQuest, Science Direct, Wiley, and the Cochrane Controlled Register of Trials (CENTRAL) was conducted. Reviewed studies were as follows: articles published from January 2015 to August 2019, with full text in English, featuring randomized controlled trials (RCTs), and patients with a diagnosis of heart failure, and self-management education interventions with follow-up. Results: Eighteen articles were reviewed in this study, whose participants were predominantly male patients aged 65 years old. Types of self-management education interventions applied included: Education and Telephone Support, Disease Management Clinics, Telemonitoring, Nurse Case Management, Nurse Visits, Multimedia Based Education, and a combination of Telephone Support and Telemonitoring. Interestingly, 83% of studies involved nurses. Conclusion: A variety of choices for self-management education interventions can be applied to improve patient self-care. Patients' conditions, characteristics and needs, follow-up treatment, and the availability of education media and health professionals were important factors supporting the success of self-management education for patients with heart failure. Collaboration across multiple disciplines and professions has been proven to contribute to the success of the program.